Accounting and Auditing: A Strategic Partnership to Ensure Financial Integrity - Jaber, Alaa Shehab; Ismail, Hanan; Lateef, Amer; Lateef, Fayez (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This paper has a brief overview of strategic partnership in accounting and auditor roles that ensure acts as guardian of organizational financial integrity. It analyses how this synergy of the two largest functions adds to openness in finance, confidence and shrinkage of anomalies at the bottom line. The study investigates cooperation between accounting and auditing team members by means of an experimental approach which combines qualitative interviews with 6 focus groups and quantitative survey of 100 financial practitioners. Quantitative analysis (regression and correlation tests) reveals modification level of the accounting quality to audit effectiveness; stronger relationship between accounting and auditing functions leads to a more transparent firm with less anomalies. Lastly, the research demonstrates that it elevates stakeholder confidence in financial reports by using such techniques. The latter was also confirmed the moderating role of regulatory compliance which meant that the presence of regulation increases the effectiveness of the cooperation between accounting and auditing. This will be of importance as the outcomes highlight the need for accounting and auditing to be aligned strategically to ensure financial integrity and lead to important advice to companies and governments. Future research should explore the evolving role of technology in fostering this collaboration.